Inferior alveolar nerve reconstruction in extensive mandibular resection: Technical notes. Issue 3 (March 2021) - Manfuso, A.; Pansini, A.; Tewfik, K.; Copelli, C.
Summary: The inferior alveolar nerve (IAN) is a sensitive branch of the mandibular nerve innervating the lower lip, the chin, the buccal mucosa and the teeths. Lesions of the IAN are reported to occur in the 64, 4% of maxillo-facial procedures, leading to anesthesia, hypoestesia and/or neurogenic discomfort. An extensive segment of the nerve can be moreover removed during mandibular resection for benign or malignant pathologies. Nervous grafts can be used in these cases to restore the nerve continuity. In order to optimize the procedure and to allow a concomitant mandibular osseous reconstruction, the Authors identified several standardized steps. The technique described allows to perform confortable and safe nervous anastomoses and to reduce the risk of damage and tension during the flap insetting phases.